Hyperinfection syndrome with hypereosinophilia and chronic kidney disease: case report and review - Lopez,Noélia (2017)
Chronic kidney disease (CKD) is associated to significant infection incidence and severity, the cause of death of, approximately, 20% of end-stage renal disease patients. Close to 80% of all infections in these patients can be related to organ or tissue other than vascular access, reflecting immune system dysfunction related to several mechanisms. Strongyloides stercoralis is an endemic nematode found especially in tropical and subtropical areas. The clinical manifestations of stercoralis infection vary according to the acuity of infection and the host response, from asymptomatic to the disseminated presentation, frequently lethal. Risk factors for severe presentations are related to immunosuppression states. The authors report a case of a patient with advanced CKD of unknown etiology, who developed an exuberant eczema, respiratory symptoms and severe hypereosinophilia. The etiological study revealed a disseminated form of Strongyloides stercoralis infection with myocardia involvement, diagnosed solely by serologic testing, despite microbiological tests to identify the infective agent. In this case, the patient has evolved favorably, with remission of symptoms and cardiac features, after adequate anti-helminthic treatment. The importance of parasitic colonization and its potential harm becomes clinically more relevant when patients become immunosuppressed, as in CKD progression or in the immunosuppressive therapy setting, such as solid organ transplant rejection therapy. A brief literature review related to strongyloidiasis and immunosuppression in the CKD setting is also presented